The impact of protective masks on outdoor recreation crowding norms during a pandemic. (27th May 2022) - Rice, William L.; Reigner, Nathan; Freeman, Stephanie; Newman, Peter; Mateer, Timothy J.; Lawhon, Ben; Taff, B. Derrick
Abstract: The continued demand for outdoor recreation during the COVID-19 pandemic presents a challenge to park and protected area managers. Numerous strategies have been suggested to reduce the risk of transmission among outdoor recreationists; however, evaluations of acceptability of these strategies and their impacts on perceptions of visitor density have not been empirically examined. The purpose of this study is to examine how varying levels of protective face mask use influence acceptability of visitor density among avid outdoor recreationists. A visually based online survey distributed through the Leave No Trace email list and a resulting linear mixed model reveal a significant interaction between visitor density and levels of mask use, indicating that outdoor recreationists have different acceptable thresholds for visitor density under different levels of mask use. These findings provide park and protected area managers with the ability to make more informed policy recommendations and align messaging to visitors regarding COVID-related protective measures.